IDENTIFIKASI KEMUNCULAN MATAIR DI SITU CISANTI KECAMATAN TARUMAJAYA, KERTASARI, KABUPATEN BANDUNG - Widia Sutriani; Ibrahim Syaifuddin; Dilla Hativa; Taufan Taufan; Andri Martoni; Ridho Hambali; Yanti Novita; Muhammad Zulham; Rahma Dani Putra; Dori Eka Putra; Endah Purwaningsih (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
Bandung Basin, is an oval-shaped basin that extends east-southeast-northwest. The many springs and rapids on the hillside around the Bandung Basin, and the year-round river flow in the Bandung Basin itself shows how great the potential of water resources in the region. The purpose of this study was to determine the process of the emergence of springs in Situ Cisanti and Know the relationship of volcanic morphology with the appearance of springs in Situ Cisanti using descriptive methods, using surveys. The results obtained from this study are: The results of statistical analysis show that the formation of old volcanoes gives an estimated value of 0.90 to spring discharge, while that of young volcanoes contributes 0.95 to spring discharge and the appearance of springs in volcanic areas is increased by power from within the earth. Fault zones when regulating spring discharges, and there are two known types of fracture formation.